2018
DOI: 10.1038/s41593-018-0076-6
|View full text |Cite
|
Sign up to set email alerts
|

Memory formation depends on both synapse-specific modifications of synaptic strength and cell-specific increases in excitability

Abstract: The modification of synaptic strength produced by long-term potentiation (LTP) is widely thought to underlie memory storage. Indeed, given that hippocampal pyramidal neurons have > 10,000 independently modifiable synapses, the potential for information storage by synaptic modification is enormous. However, recent work suggests that CREB-mediated global changes in neuronal excitability also play a critical role in memory formation. Because these global changes have a modest capacity for information storage comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
236
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(244 citation statements)
references
References 71 publications
7
236
0
1
Order By: Relevance
“…Besides our in vivo data -restoring cognitive performance in the Y-Maze -we also show that BDNF rescues the LTP impairment observed in IL-17 -/-and TCRδ-/-mice. LTP is the main form of synaptic plasticity reflecting the activity of synaptic information storage processes, and has been often used as the gold standard cellular correlate of learning and memory in the hippocampus (43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Besides our in vivo data -restoring cognitive performance in the Y-Maze -we also show that BDNF rescues the LTP impairment observed in IL-17 -/-and TCRδ-/-mice. LTP is the main form of synaptic plasticity reflecting the activity of synaptic information storage processes, and has been often used as the gold standard cellular correlate of learning and memory in the hippocampus (43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the balance of inhibition and excitation, a number of other functional properties might be expected to modulate the oPDT, the oADT, or both. Synaptic strength determines the threshold for downstream propagation of the synchronous discharge (Nicoll, 2017), intrinsic excitability modulates the responsiveness of downstream cells, which is governed by the relative expression and cellular localization of voltage-gated Na + , K + , and Ca 2+ channels (Graef and Godwin, 2010;Lisman et al, 2018;Meadows et al, 2016), and the regulation of the extracellular space by glia (Devinsky et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…How does CREB activation by phosphorylation and CBP association confer neuroprotection remains unclear. Moreover, reports that this mode of CREB activation confers neuronal hyper excitability (Dong et al 2006;Soriano et al 2006;Yiu et al 2014;Lisman et al 2018) and cause neurodegeneration (Lopez de Armentia et al 2007;Valor et al 2010;Benito et al 2011) suggest that indiscriminative hyperactivation of CREB is unlikely to be productive and a neuroprotective approach in excitotoxicity. A number of recent studies have shown that in some important cases the non-canonical pathway is at play, involving CREB stabilization on the DNA by CRTC.…”
Section: Discussionmentioning
confidence: 99%